Description of three new genera, five new species and some additional data on the taxonomy and distribution of Neotropic Eriococcidae (Homoptera Coccoidea Eriococcidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Three new genera, five new species are described, two genera are resurrected, two species are redescribed, nine new combinations are proposed. Some new data are given to the knowledge of the family Eriococcidae from Chile, Costa Rica, Ecuador, Paraguay, and Peru. These new data show that the family needs a wider study in the region.
Keywords: scale insects; Hemiptera; Coccoidea; Eriococcidae; new genera; new species; new combinations; redescription; Acanthococcus; key for genera and species